Integration of Renewable Energies and its Impact on Electricity Price (2017)
Non-conventional sources of renewable energy (NCER) are energy sources considered as a clean alternative for the energy supply versus an electric generation based on fossil fuels. In addition, they are a way by which the concentration level in the market is reduced and the participation of the demand can be given. This article presents different mechanisms of integration of these sources in the market, and analyzes their effect on the electricity price in Colombia. Under defined simulation conditions, the results indicate that a 20% hare of the USRE in the coverage of demand on a distributed basis generates a 22% reduction in the electricity price for a long term.